Sosialisasi Administrasi Kependudukan Dalam Rangk Penyelenggaraan Sistem Jaminan Kesehatan UHC (Universal Health Coverage) Di Desa Batu Putih, Kecamatan Sekotong, Kabupaten Lombok Barat - Ramdani Abd. Hafizh; Siti Yulianah M. Yusuf; Basuki Sri Hermanto; Syaumudinsyah; Nia Kurniati (CV. Multi Kreasi Media, 2024)
Health is an important human right, and Universal Health Coverage (UHC) is an integral part of realizing this right. The Indonesian government has also accelerated the coverage of UHC participants through Presidential instructions. The commitment to encourage UHC is not only central but also regional, involving all ministries/institutions and regional governments as well as the role of the community in realizing equal and quality access to health services for all. Based on this, it is necessary to carry out community service activities in the form of socialization of population administration in the context of implementing the UHC (Universal Health Coverage) Health Insurance system in Batu Putih Village, Sekotong District, West Lombok Regency.